Keberhasilan Pembelajaran dilihat dari Pengaruh Psikologi pada Siswa Sekolah Menengah Kejuruan di Palembang - AKHMAD SAYUTI (Jurnal Pelita Pendidikan, 2024)
This research aims to analyze the influence of psychological factors such as motivation, self-efficacy, stress and anxiety on the learning success of Vocational High School (SMK) students. Quantitative and qualitative approaches are used to gain a comprehensive understanding of the relationship between these factors and student learning outcomes. The research participants consisted of 300 vocational school students from various majors and grade levels, who were chosen randomly. Data were collected using validated questionnaires to measure motivation, self-efficacy, academic stress, and academic anxiety. Additionally, in-depth interviews were conducted with teachers to obtain their perspectives on the influence of psychological factors on student learning. The research results show that there is a significant positive correlation between motivation and self-efficacy and learning success. Students with high motivation and self-efficacy tend to achieve better learning outcomes. In contrast, stress and anxiety have a significant negative correlation with learning success, where high levels of stress and anxiety are associated with lower academic achievement. Regression analysis revealed that learning motivation and self-efficacy made a significant positive contribution to learning success, while stress and anxiety had a significant negative effect. Interviews with teachers support these quantitative findings, showing that psychological factors greatly influence student participation and performance in learning. In conclusion, psychological factors such as motivation, self-efficacy, stress and anxiety play an important role in the learning success of vocational school students. Therefore, effective learning strategies must pay attention to and support students' psychological health to maximize their academic potential. The results of this research provide insight into the development of programs that can improve students' mental and emotional well-being, as well as increase the effectiveness of the teaching and learning process in vocational schools